2012
DOI: 10.5504/bbeq.2011.0137
|View full text |Cite
|
Sign up to set email alerts
|

Fructooligosaccharide Intake Alters the Phospholipid and Fatty Acid Composition of Liver Plasma Membranes

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…The obtained results showed that the content of cholesterol, expressed as mol%, was slightly reduced in membranes from inulin-fed rats. This finding is in accordance with our previous data obtained with rats on fructooligosaccharide (FOS)-enriched diet, which revealed a more marked decrease of cholesterol in liver plasma membranes [ 11 ]. In these investigations, we also established a lower degree of cholesterol oxidation, as well as a lower level of lipid peroxides in FOS-fed rats.…”
supporting
confidence: 93%
“…The obtained results showed that the content of cholesterol, expressed as mol%, was slightly reduced in membranes from inulin-fed rats. This finding is in accordance with our previous data obtained with rats on fructooligosaccharide (FOS)-enriched diet, which revealed a more marked decrease of cholesterol in liver plasma membranes [ 11 ]. In these investigations, we also established a lower degree of cholesterol oxidation, as well as a lower level of lipid peroxides in FOS-fed rats.…”
supporting
confidence: 93%
“…However, quite a few studies are devoted to the impact of prebiotics on liver membrane lipids, their metabolism, and susceptibility to peroxidation. In our previous studies, we reported alterations in liver membrane lipid composition and structural organization as a result of the intake of fructooligosaccharides [ 24 ]. In the present study, we analyzed the impact of XOS intake on the lipid composition and susceptibility to the oxidative attack of cholesterol, the latter being altered in the liver plasma membranes of XOS-fed rats.…”
Section: Resultsmentioning
confidence: 99%